Pour une écologie politique des savoirs. Comment hériter du domaine STS (Sciences, technologies et société) ? - Antoine Lalande; Joëlle Le Marec (Les Cahiers de Framespa)
In this article, we would like to discuss the necessity, felt by many authors, to seriously consider the idea of « zombies » categories and technologies. Indeed, the aim here is to deal with the sciences’ conditions of heritage in Anthropocene context. By focusing on the case of human and social sciences, and by reconnecting with the political history of STS, the issue is on one hand to preserve the relations and experiences of knowledges that we feel as « alive ». But, on the other hand, the problem is also to think about the way we could unestablish them from the practices and relations that participate to zombify or enroll them in deadly processes. After showing how this project joins up with the idea of a political ecology of knowledges, we demonstrate in a first time how this issue inherits the epistemological and political questions that characterized the rise of french STS in the 1970’s. Then, we will resume our personal studies so as to show that the « alive » or « zombying » conditions of knowledges are something that can only be felt from inquiry. More specifically, this feeling is above all present in the meetings’ situations with socials sciences’ publics. In this way, we would like to stand for the idea that inquiry can be the foundation of a collective initiative from which put into practice a political ecology of knowledges. Thereby, this ecological project would consist in plumbing the « living » ou « deadly » dimensions of sciences in society, from their places of professional production to their fringes.